2018
DOI: 10.13048/jkm.18012
|View full text |Cite
|
Sign up to set email alerts
|

A Proposal for Standardization of Acupotomy Terms and Definition Among Korean researchers

Abstract: The aim of this study was to investigate the use of Korean and English terminology of acupotomy therapy among Korean Researchers. Methods: The search was conducted on eight medical journals (PubMed, EMBASE, Cochrane Library, OASIS, KISS, IMR, NDSL, RISS), Google Scholar and 8 Korean medine journals. The definitions of acupotomy therapy, Korean and English terminology were analyzed in the studies that met the criteria. Results: A total of 60 studies were finally included in the analysis. In Korean terminology, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In addition, the acupotomy treatment exfoliates the chronically damaged adhesive tissues from soft tissues, peritendineum, muscles or ligaments, and exerts a mechanical stimulation in order to dilate the microcirculatory system to increase nutritional supply to tissue lesions, releasing the constraints of the muscles, thereby inducing local recovery [4]. There were 60 papers associated with acupotomy that were published before February 12, 2018, 33 reports discussed soft tissue, osseous tissue and pain triggering points in skeletal muscles, and 27 did not specify the lesion [17]. Acupotomy treatment can be seen to be highly adaptable to muscular skeletal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the acupotomy treatment exfoliates the chronically damaged adhesive tissues from soft tissues, peritendineum, muscles or ligaments, and exerts a mechanical stimulation in order to dilate the microcirculatory system to increase nutritional supply to tissue lesions, releasing the constraints of the muscles, thereby inducing local recovery [4]. There were 60 papers associated with acupotomy that were published before February 12, 2018, 33 reports discussed soft tissue, osseous tissue and pain triggering points in skeletal muscles, and 27 did not specify the lesion [17]. Acupotomy treatment can be seen to be highly adaptable to muscular skeletal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The term and technique of acupotomy remains controversial in Korea however, a 2018 study by Yoon et al [18] revealed that the following acupotomy terms Chimdochimsul (37 studies, 66.07%), Dochim (23 studies, 41.07%) are the most widely used in Korea. In English, acupotomy (46 studies, 76.66%), and miniscalpel acupuncture (10 studies, 16.66%) are most widely used.…”
Section: Search Strategymentioning
confidence: 99%
“…It has been used continuously by many Korean medicine doctors since the official medical device registration in 2002. It is easy to perform, effective, and less painful than surgery; therefore, it is actively used to treat chronic pain conditions/ diseases by detaching, or incising soft tissues [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%